ANALISIS PENERAPAN KURIKULUM MERDEKA DALAM MENINGKATKAN KREATIVITAS SISWA DI MIS HUMAIROH LABUHANBATU UTARA - Mursal Aziz; M. Walimsyah Sitorus; Cici Novianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The curriculum is a tool to achieve educational goals and guidelines in implementing learning in all types and levels of education. In the world of education, the curriculum must also be understood in depth so that the educational process can run systematically and smoothly so that the planned educational goals can be achieved. This study aims to determine the process of implementing the independent curriculum in learning at MIS Humairah Labuhabatu Utara with the aim of increasing student creativity and of course also improving the quality of education for students. The method used in this study is a qualitative approach. The type of research used in this study is field research. The results of the study indicate that MIS Humairah Labuhanbatu Utara school has not succeeded in implementing the independent curriculum to improve student creativity. If the socialization of the independent curriculum is carried out well by the relevant parties. Certainly the school will also be ready to implement the independent curriculum at MIS Humairah Labuhanbatu Utara. To optimize the implementation of the independent curriculum, teachers also need to develop competencies through training/workshops. So that teachers will provide quality education to students and can increase creativity in students.